Pengaruh Manajemen Kas terhadap Profitabilitas dan Likuiditas Perusahaan Aneka Industri yang Terdaftar di BEI - Ramadila, Dina; Denny Erica; Siti Mabrur Rachmah (Jurnal Sistem Informasi Akuntansi (JASIKA), 2023)
The purpose of this research is to empirically establish the relationship between cash management and the profitability and liquidity of manufacturing firms in the Industrial Anek Sector that are traded on the Indonesia Stock Exchange (IDX). In this analysis, we employ the current ratio, quick ratio, and return on assets. The years 2020 and 2022 were chosen for this analysis. This study is a quantitative statistical analysis. The population of this analysis consists of the many different types of manufacturing that will be traded on the Indonesia Stock Exchange (IDX) between 2020 and 2022. Purposive sampling was employed to choose the sample. There are ten businesses that are a good fit for the requirements. Methods of regression analysis and conventional assumption testing were applied in this investigation. This research shows that between 2020 and 2022, Cash Management will not significantly affect the bottom lines of businesses across different sectors. Keywords: Cash Management, Profitability, Liquidity.